Updated Review on Ozone Therapy in Pain Medicine - Hidalgo-Tallón, Francisco Javier; Torres-Morera, Luis Miguel; Baeza-Noci, Jose; Carrillo-Izquierdo, Maria Dolores; Pinto-Bonilla, Rosa (Frontiers in Physiology, 2022)
The use of medical ozone in the treatment of chronic pain is progressively expanding in Spain and today it is used both in public and private medical centers. However, there is a great lack of knowledge about this technology not only in primary care but also in medical specialties. Although its biochemical bases are well determined and there are various systematic reviews and meta-analyses in the literature that justify its use in pain medicine, some professionals still are prejudiced against it. In this paper, we have done a review on ozone therapy in pain medicine, compiling the evidence published about it.